High-Power Distance Is Not Always Bad: Ethical Leadership Results in Feedback Seeking - Gong, Zhenxing; Van Swol, Lyn; Xu, Zhiyuan; Yin, Kui; Zhang, Na; Gul Gilal, Faheem; Li, Xiaowei (Frontiers in Psychology, 2019)
Feedback seeking relates positively to organizational identification and task performance. However, an individual generally views seeking feedback as risky. It remains unclear whether, why, and when ethical leadership impacts on feedback-seeking behavior. This research aimed to explore the mediating role of psychological safety in the relationship between ethical leadership and nurses’ feedback-seeking and to further explore the moderating effect of power distance in this mechanism. After eliminating invalid surveys, the sample included 458 pairs. The SPSS PROCESS macro was used for the data analysis. The results indicate that ethical leadership positively affected nurses’ feedback-seeking. Ethical leadership influences feedback-seeking through psychological safety. With high power distance, ethical leadership significantly positively influenced psychological safety and then positively affected feedback-seeking behavior. In sum, in the context of high-power distance, ethical leadership is especially important for psychological safety and feedback-seeking behavior.